Studi Literature Review: Keterampilan Bahasa dan Bentuk-Bentuk Penilaiannya - Barkah; Ardian, Teofilus; Sudiana, I Nyoman; Putrayasa, Ida Bagus (Nusa Putra University, 2025)
The study explores the development of language skills and assessment methods in Indonesian elementary education. Language skills are foundational for academic and social success, yet significant gaps remain in meeting basic competency standards. This research aims to evaluate the impact of language skills on students' academic achievements and to advocate innovative assessment techniques for improving educational outcomes. A literature review approach was adopted, drawing data from books, national and international articles, and other relevant sources. The study focused on analyzing the role of language skills and the effectiveness of various assessment forms, such as formative and summative evaluations, and performance-based assessments. The findings highlight significant deficiencies in students’ language skills, with only 60% meeting competency standards. Conventional evaluation methods, predominantly written tests focused on cognitive levels C1 and C2, fail to address students' comprehensive needs. Innovative approaches, such as formative assessments, dynamic evaluations, and performance-based assessments, show potential for holistic skill development. The study also underscores the importance of teacher training in adopting these advanced assessment methods. Performance-based assessments allow students to demonstrate language skills in practical contexts, fostering real-world applicability. Dynamic evaluations emphasize interactive processes, offering scaffolding support to enhance learning. However, implementing these methods requires overcoming barriers such as limited teacher expertise and traditional mindsets in educational institutions. Enhancing evaluation methods and teacher training can significantly improve language skills among elementary students, leading to better academic and social outcomes. By integrating innovative assessment techniques, this study provides a roadmap for bridging competency gaps and achieving meaningful educational progress in Indonesia.